PEMBUATAN PRODUK SABUN CAIR DARI ECO-ENZYME DI KELURAHAN ANDALAS KECAMATAN PADANG TIMUR KOTA PADANG - Purnawan Pontana Putra; Fatma Sri Wahyuni; Yelly Oktavia Sari; Erizal Erizal; Dachriyanus Dachriyanus; Yufri Aldi; Dedy Almasdy; Salman Salman (LPPM Universitas Andalas, 2023)
Eco-Enzyme, a multifunctional liquid produced from a mixture of organic waste such as vegetables, fruits, brown sugar, coconut sugar, corn sugar, sugarcane, and water that has undergone fermentation, has various benefits for the environment and human health. Eco-Enzyme contains beneficial enzymes that accelerate biochemical reactions in the environment. The enzymes found in Eco-Enzyme can be used for various applications, such as organic liquid fertilizer for plants, an additive in detergents, floor cleaners, pesticide residue cleaners, and rust removers. Using Eco-Enzyme as a liquid soap can help reduce soil pollution. Meanwhile, using Eco-Enzyme as a cleaning agent can help reduce the use of hazardous chemicals that damage the environment. This integrated program is carried out in three stages: the first is to socialize the benefits of using Eco-Enzyme, the second is to make Eco-Enzyme, and the third is to make soap from Eco-Enzyme. The production of Eco-Enzyme begins with the collection of organic waste consisting of fruit and vegetable waste, which is then mixed with brown sugar and water and left to ferment for three months. After the Eco-Enzyme product is ready, soap-making uses ingredients such as potassium hydroxide (KOH), coconut oil, cooking oil, distilled water, orange-scented perfume, and Eco-Enzyme. Training on Eco-Enzyme and soap making is conducted in the Andalas Subdistrict, which is welcomed enthusiastically by the local community. This program is expected to serve as a reference for transforming organic waste into more practical and environmentally friendly sustainable products.